The management of community extension projects of vocational schools in Eastern Visayas. IN Dissertation abstracts [column] - Lagdaan, Ernesto D. (1987)
This study was an attempt to determine the adequacy of management of the school-initiated community extension projects of vocational schools in Eastern Visayas, as perceived by the respondents, namely: school administrators, extension coordinators, teacher implementors, and clientele.
The researcher used a structured questionnaire to gather the data regarding adequacy of identification, organization, implementation, termination and evaluation activities in the management of the projects.
The findings of the study reveal that in agricultural schools, goat raising had the most number of clientele, while crop rotation and orchard raising had the least number of clientele. In fishery schools, the most popular project was fish preparation, and the least popular was fish culture. In trade schools, the most popular was beauty culture, while the least attended was practical electricity.
Keywords: Extension programs